2016
DOI: 10.1039/c6cp02475k
|View full text |Cite
|
Sign up to set email alerts
|

Flexibilities of isoindoline-derived spin labels for nucleic acids by orientation selective PELDOR

Abstract: Pulsed electron electron double resonance experiments with rigid spin labels can reveal very detailed information about the structure and conformational flexibility of nucleic acid molecules. On the other hand, the analysis of such data is more involved the distance and orientation information encoded in the time domain data need to be extracted and separated. In this respect studies with different spin labels with variable internal mobility are interesting and can help to unambiguously interpret the EPR data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…EPR spectroscopy has emerged as an excellent tool for investigating such systems, since it does not require crystallization, and its performance is independent of protein size . EPR requires paramagnetic probes; for diamagnetic systems, site‐directed spin labeling (SDSL) is currently widely used in biophysical research .…”
Section: Introductionmentioning
confidence: 99%
“…EPR spectroscopy has emerged as an excellent tool for investigating such systems, since it does not require crystallization, and its performance is independent of protein size . EPR requires paramagnetic probes; for diamagnetic systems, site‐directed spin labeling (SDSL) is currently widely used in biophysical research .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, owing to limited spectral excitation, multiple experiments are often required to resolve a single distance. There has also been a large effort to develop spin labels that require less post‐synthesis modification ,,. However, these labels position the nitroxide away from the duplex, further complicating data analysis.…”
Section: Figurementioning
confidence: 99%
“…While potential problems associated with the use of large fluorescent labels, such as GFP mutants have been discussed [1113] , the conjugation of small organic fluorophores is usually thought to have negligible effects. A few studies have already shown the effect of fluorophore attachment to nucleic acids [810,14,15] and some deal with the effects of dyes on certain protein characteristics [14,16,17] . For example, Dallmann et al modified DNA oligomers with 2-aminopurine and investigated their structural changes by 2D NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is not unique to labeling of proteins with fluorescent dyes, but extends to other types of protein tagging methods as well. For example, in NMR and EPR studies, paramagnetic tagging with spin labels (e.g., IPSL, MTSSL), lanthanide chelating tags (e.g., DOTA, DTPA, EDTA), or lanthanide binding tags (LBTs), are regularly used for investigation of structure, dynamics, and function of proteins and protein–ligand interactions. To date, fluorescent proteins are frequently used in fusion constructs with proteins of interest to be studied due to the straightforward genetic encoding for expression in cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation